The Effect of Couple-centered Counseling on Sexual Self-concept and Sexual Violence in Pregnant Women - Saeideh Sabzeei; Seyedeh Zahra Masoumi; Farideh Kazemi; Mansoureh Refaei; Mohammad Haghighi (Journal of Holistic Nursing and Midwifery)
Introduction: Sexual violence during pregnancy causes adverse physical and psychological consequences for pregnant women and their fetuses. Objective: This study aimed to explore the effect of couple-centered counseling on sexual self-concept and violence among pregnant women. Materials and Methods: This randomized controlled clinical trial with two groups (26 women in each group) was conducted on pregnant women exposed to sexual violence who lived in Hamadan City in the west of Iran. The mothers exposed to sexual violence were randomly assigned to two groups. Data were collected using the sexual violence and the sexual self-concept questionnaires. For the experimental group, 6 one-hour couple counseling sessions were held. After the end of the sessions, the study questionnaires were completed again by two groups. Data analysis was done using the chi-square, Fisher exact, independent t-test, paired t-test, and analysis of covariance tests. The significance level of the tests was considered 0.05. Results: The Mean±SD age of pregnant women in the intervention group was 28.65±5.96, and in the control group was 28.77±6.73 years; the mean age of the spouses in the intervention group was 33.62±6.05 and in the control group was 35.04±7.34 years. The results showed that the mean scores of sexual violence after the intervention were 26.10±2.04 in the intervention group and 35.08±2.04 in the control group (P=0.001, Cohens’ d=4.40). The Mean±SD scores of sexual self-concept after the intervention were 8.13±2.02 in the intervention group and 13.33±2.02 in the control group (P=0.001, Cohens’ d=2.57). Moreover, the intervention group experienced a significant decrease (P=0.001) in the dimensions of negative sexual self-concept, including anxiety, fear, monitoring, and depression (P=0.001). Conclusion: According to these results, couple-centered counseling has effectively reduced sexual violence and negative sexual self-concept by raising couples’ awareness.